There is no Home. Cultural Landscape in Literature (selected examples) - Peroń, Małgorzata (Porównania, 2021)
The article covers issues related to cultural geography and its relations with literature. In the meeting of these domains, issues related to geopoetics, memory space and narratives about identity arise. The text presents literary transpositions of experiences of people who have memories connected with losing their home. They are confronted with the family landscape. Literary works and personal memories show the concept of a symbolic understanding of landscape (Żeromski, Iwaszkiewicz, Miłosz). Monika Sznajderman in her book Empty Forest recreates the memory of places from which people were displaced. The writer’s voice becomes the voice of the guardian of the memory of their harm. Reading the meanings hidden in the landscape leads to discovering personal biographies and the history of nations and ethnic minorities.